Pengaruh Berita Ekonomi dan Sentimen Investor Terhadap Minat Investasi Mahasiswa di Pasar Modal - Lalu Ahmad Ramadani; Sabrang Gilang Gemilang; Muhammad Helmy Reza (Universitas Islam Negeri Mataram, 2026)
The development of information technology has provided wider access to the capital market and has encouraged a growing interest in investment among university students. Exposure to economic news and market sentiment circulating among investors becomes an external factor that may influence students’ perceptions and investment decisions. This study aims to analyze the influence of economic news and investor sentiment on the investment interest of students in the Capital Market Study Group (KSPM) NTB for the period of 2023–2024. The research method used is a quantitative approach with an associative research type, and data analysis was conducted using multiple linear regression. The results show that, partially, the economic news variable (X₁) has a significant effect on investment interest (Y), with a t-value of 7.235 > t-table value of 1.669 and a significance level of 0.000 < 0.10. The investor sentiment variable (X₂) also has a significant effect on investment interest (Y), with a t-value of 6.045 > t-table value of 1.669 and a significance level of 0.000 < 0.10. Simultaneously, both variables significantly influence students’ investment interest, with an F-value of 200.703 > F-table value of 2.39 and a significance level of 0.000 < 0.10. Therefore, it can be concluded that economic news and investor sentiment are important external factors that significantly encourage students’ interest in investing in the capital market.